Application value of three-dimensional arterial spin labeling perfusion imaging in investigating cerebral blood flow dynamics in normal full-term neonates - Jia-Ning Wang; Jia Li; Huai-Jun Liu; Xiao-Ping Yin; Huan Zhou; Ya-Ting Zheng; Na An; Si Liang; Zuo-Jun Geng (BMC Pediatrics, 2019)
Abstract Background This study aims to investigate the application value of three-dimensional arterial spin labeling (3DASL) in investigating cerebral blood flow dynamics in full-term neonates. Methods A total of 60 full-term neonates without known intracranial pathology were recruited for 3DASL examination. These neonates were divided into three groups: 1–3 day group, 4–7 day group, and 8–15 day group. On the cerebral blood flow (CBF) images, regions of interest (ROI) were selected from the frontal white matter, parietal white matter, basal ganglia, corona radiata, thalamus and brainstem, and the CBF values of each ROI were recorded. The CBF values of ROIs at bilaterally symmetric locations, the values of each ROI between males and females, and the values of each ROI among these three different age groups were compared. Results The difference in CBF values of the frontal white matter, parietal white matter, basal ganglia, corona radiata and thalamus at the bilateral symmetric positions were not statistically significant. There was no statistical difference in the CBF values of each brain region between the male and female groups. The CBF values at the basal ganglia region, corona radiata and parietal white matter were higher in the 8–15 day group, when compared to the 1–3 day and 4–7 day groups (P < 0.05). The CBF value at the basal ganglia region was higher in the 4–7 day group, when compared to the 1–3 day group (P < 0.05). The CBF value at the frontal white matter was lower in the 4–7 day group, when compared to the 1–3 day and 8–15 day group (P < 0.05). The CBF value at the brainstem was higher in the 4–7 day group, when compared to the 1–3 day and 8–15 day groups (P < 0.05). Conclusion The 3DASL can quantitatively measure CBF, and be used to evaluate cerebral hemodynamics in neonates. The basal ganglia region and corona radiata CBF increases with the increase in neonatal diurnal age.